The effect of short-term royal jelly supplement on testosterone levels in sedentary and healthy individuals: Royal jelly and testosterone - Taşdoğan, Ali Muhittin; Pancar, Zarife; Özdal, Mustafa; Vural, Mehmet; Pancar, Serkan; Birinci, Yakup Zühtü (Progress in Nutrition, 2020)
This study with a placebo-controlled experimental design intends to investigate the effect of Royal Jelly (RJ) on the testosterone levels in sedentary men at a dose of 1000 mg/day. For this purpose, a total of 20 adult sedentary men aged 21 to 23 were included in this study. The subjects visited the laboratory every day for 15 days between 08:00 and 10:00 to get their portion of royal jelly. The subjects were randomly divided into two groups, namely the experimental group (n = 10 individuals, 1000 mg/day of Royal Jelly) and the placebo group (n = 10 individuals, corn starch mixed with 1000 mg/day of water) and they took royal jelly in glass vials at the same time. Blood samples were taken from both groups of subjects one day before and one day after the study and analyzed to determine their testosterone levels. 2x2 mixed factor ANOVA and LSD tests were used to analyze data obtained from the experimental and the placebo group. A sharp increase in the testosterone levels of the experimental group that took RJ for a short time was found to be statistically significant (p<0.05). The pre- and post-test values of the placebo group were not found to be statistically significant (p>0.05). The study shows that a 1000 mg/day dose of RJ supplements was effective in increasing testosterone levels in sedentary, healthy men.